PEDAGOGICAL CONDITIONS OF FORMING FUTURE PRIMARY SCHOOL TEACHERS' READINESS TO USE DISTANCE LEARNING TOOLS - Voloshyna, Olha (Collection of scientific papers «ΛΌГOΣ», 2023)
In the context of the development of scientific and technological progress in the education system with the involvement of modern computer technologies, the field of training future teachers also requires fundamental changes. Among the key competences defined in the new State Standard of Education of Ukraine (2016) is information and communication (information and digital) competence, which includes the confident use of information and communication technologies (ICT) to create, search, process and exchange information in the workplace, in public space and in private communication. ICT competence also includes information and media literacy, programming basics, algorithmic thinking, database manipulation, development of Internet and cybersecurity skills, and an understanding of ethics (e.g. copyright, intellectual property) when working with information [1]. Thus, the new Ukrainian school needs teachers who can ensure the development of information and communication (ICT) skills in prepared and motivated students. One of the most effective ways to achieve this is through the use of distance education technologies. Mastery of distance learning technologies is becoming a prerequisite for further professional development, particularly in the field of education. Currently, research by domestic and foreign scientists is aimed at identifying a number of conditions for the introduction of distance technologies in the educational process in higher education and ensuring its effectiveness [2]. However, it should be noted that at this stage of education development, there is no single list of conditions for the formation of future primary school teachers' professional readiness to use distance education tools.